2014
DOI: 10.2478/jcbtp-2014-0016
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Analysis of the Impact of Inflation Targeting on the Risk Premium

Abstract: The basis for the conduct of monetary policy is monetary policy strategy. Monetary strategy is necessary for monetary policy makers to analyse all relevant information in order to undertake effective policy actions. Inflation targeting has enabled countries to achieve low inflation in the very short term. Due to this, the financial markets have adjusted their long-term inflation expectations and incorporated them into the interest rate. Risk premiums that compensate for the uncertainty of inflation have fallen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…The global financial cycle transforms the trilemma into a "dilemma" or an "irreconcilable duo": independent monetary policies are possible if and only if the capital account is managed. Krušković and Maričić (2014) examine how the adoption of inflation targeting affects the movement of the risk premium. The hypothesis they want to test is that the adoption of inflation targeting affects the reduction of the country risk premium by affecting the formation of a more stable macroeconomic environment through a more stable and predictable inflation rate in the medium and long term.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The global financial cycle transforms the trilemma into a "dilemma" or an "irreconcilable duo": independent monetary policies are possible if and only if the capital account is managed. Krušković and Maričić (2014) examine how the adoption of inflation targeting affects the movement of the risk premium. The hypothesis they want to test is that the adoption of inflation targeting affects the reduction of the country risk premium by affecting the formation of a more stable macroeconomic environment through a more stable and predictable inflation rate in the medium and long term.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Umar, Dahalan, and Aziz (2016) showed that the Reserve Bank of South Africa adopted inflation targeting framework and could boost the economy. Kruskovic and Maricic (2014) found that the adoption of inflation targeting affects the reduction of the country risk premium by making a more stable macroeconomic environment through a more stable and predictable inflation. Monadjemi and Lodewijks (2014) indicated that inflation targeting was effective prior to the financial crisis around the year of 2008, and a more flexible form of targeting may still be appropriate after the crisis.…”
Section: Existing Studies About Inflation Targetingmentioning
confidence: 99%
“…The set of monetary instruments employment will always differ from country to country and region to region. However, while price stability is first and foremost the primary objective of monetary policy, [8] argues that exchange rate stability and the growth of output and employment should not be forgotten as part of the objectives of the monetary policy.…”
Section: Introductionmentioning
confidence: 99%